PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DAN KEMITRAAN INDUSTRI TERHADAP EMPLOYABILITY SKILLS SISWA DI SMK MUHAMMADIYAH 7 GONDANGLEGI - Rizky Ardian Khoirul Putera; Sri Harini; Muh. Hambali (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the influence of principal's transformational leadership and industrial partnerships on students' employability skills at SMK Muhammadiyah 7 Gondanglegi. Motivated by the high unemployment rate among vocational high school graduates, which indicates a competency gap between graduates' skills and industry demands, this study employed a quantitative correlational approach using a survey technique. The population consisted of 1,340 eleventh and twelfth-grade students, with a sample of 136 respondents selected through proportional sampling. Data were collected using a valid and reliable Likert-scale questionnaire. Data analysis was performed using Ordinal Logistic Regression with SPSS 26. The results showed that both principal's transformational leadership and industrial partnerships significantly influence students' employability skills. The Nagelkerke value of 0.814 indicates that both variables together explain 81.4% of the variance in employability skills. The novelty of this research lies in the simultaneous integration of both variables within the context of vocational education using the Ordinal Logistic Regression approach.